TRADISI ADAT PERNIKAHAN SUKU BANJAR DI DESA PENGALIHAN KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Wahyuni, Lely; Isjoni, Isjoni; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Tradition It is the custom of society that is often carried out by a group of people from generation to generation from generation to generation and still continues to this day. Banjar wedding customary tradition is a tradition carried out by Banjar Pengalihan people. This study aims, To find out the process of Indigenous Tradition of Banjar Tribe marriage in Pengalihan Village, Keritang Subdistrict, Indragiri Hilir Regency, To find out the kinds of Indigenous Traditions of the Banjar Tribe marriage in the Pengalihan Village, Keritang District, Indragiri Hilir The Banjar tribe comes from Sumatran, Kalimantan and Javanese Malays who came to South Kalimantan to trade. Their customs and beliefs are due to the centuries-old influence of Dayaks, Malays and Javanese. That Banjar culture in the community area of his hometown is indeed very dominating, it can be seen in daily life and cultural arts. Banjar arts such as Bamanda, Balamut, Madihin, Japen, are still often performed at certain events in connection with celebrating holidays, celebrating weddings, festivals, or other forms of celebration after the harvest season. Based on records, the population in Indragiri Hilir Regency is around 560 thousand people, 40 percent of them are Banjar tribes, followed by Malays, Bugis, Minang, Javanese and other ethnic groups. Regency, knowing the development of the kinds of Indigenous Traditions of the Banjar Tribe marriage in the Pengalihan Village, Keritang District, Indragiri Hilir Regency. In this study using qualitative research methods. Qualitative is a method that does not use numbers in data collection and in giving an interpretation of results. The results of this study indicate that the tradition of the Banjar tribe marriage tradition is one of the indigenous Banjar tribes whose fiber will mean.Key Words: Tradition, Customary Marriage